Assessment of the peripheral microcirculation in patients with and without shock: a pilot study on different methods - Filho, Roberto Rabello (J Clin Monit Comput, 2019)
Microvascular dysfunction has been associated with adverse outcomes in critically ill patients, and the current concept of hemodynamic incoherence has gained attention. Our objective was to perform a comprehensive analysis of microcirculatory perfusion parameters and to investigate the best variables that could discriminate patients with and without circulatory shock during early intensive care unit (ICU) admission. This prospective observational study comprised a sample of 40 adult patients with and without circulatory shock (n = 20, each) admitted to the ICU within 24 h. Peripheral clinical [capillary refill time (CRT), peripheral perfusion index (PPI), skin-temperature gradient (Tskin-diff)] and laboratory [arterial lactate and base excess (BE)] perfusion parameters, in addition to near-infrared spectroscopy (NIRS)-derived variables were simultaneously assessed. While lactate, BE, CRT, PPI and Tskin-diff did not differ significantly between the groups, shock patients had lower baseline tissue oxygen saturation (StO(2)) [81 (76–83) % vs. 86 (76–90) %, p = 0.044], lower StO(2)min [50 (47–57) % vs. 55 (53–65)  %, p = 0.038] and lower StO(2)max [87 (80–92) % vs. 93 (90–95) %, p = 0.017] than patients without shock. Additionally, dynamic NIRS variables [recovery time (r = 0.56, p = 0.010), descending slope (r = − 0.44, p = 0.05) and ascending slope (r = − 0.54, p = 0.014)] and not static variable [baseline StO(2) (r = − 0.24, p = 0.28)] exhibited a significant correlation with the administered dose of norepinephrine. In our study with critically ill patients assessed within the first twenty-four hours of ICU admission, among the perfusion parameters, only NIRS-derived parameters could discriminate patients with and without shock. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10877-019-00423-8) contains supplementary material, which is available to authorized users.